Karya Sastra sebagai Sumber Sejarah Bangsa - I. B. Putera Manuaba (HISKI, 2009)
Works of literature are multidimensional works which deliver various problems of human life. The vertical relationship between human and the creator and the horizontal relationship between human and the universe are pictured in these works. Therefore, the functions of literature are not only important for writers, but also for those of other disciplines like sociology. politics, psychology and history. While from its own perspective literature is an aesthetic object, for other disciplines it becomes a social document and an ephiphenomenon (second phenomenon). In the field of history, literature is not only a social document and the second phenomenon, but often it also serves as a source of history of the nation his becomes possible for in their creative processes writers do observations, experience the life and take notes of whatever happens in their time. As an individual and a member of society, they do internalizalions and social interactions, and then express them in their works Thus, literature appears to be a source of history of the nation, revealing the spirit of its time. Consequently, studying literature may also mean studying history of the nation. Writers write history in their own versions, which may be closer to the historical reality. The works that speak about nationalism through characters in storiess can arouse the spirit of the nation since they give historical spirit and data. The works of Pramoedya Ananta Toer and Y.B. Mangunwijaya, for example, become important historical works because they contain a lot of values ot the nation.